A Life Quality Architectural Approach to Enhance Digital Skills Training - Marin, Iuliana; Popovici, Dorina; Grivokostopoulou, Foteini; Koutsojannis, Constantinos (Proceedings of the Life Improvement in Quality by Ubiquitous Experiences Workshop (LIQUE); 2021: Proceedings of the 1st Life Improvement in Quality by Ubiquitous Experiences Workshop, 2021)
The paper presents the demand for professional services and skills in the health sector. The Erasmus+ DIGI4ME project aims to enhance digital skills trainings. An analysis of the Romanian health information system was conducted based on the interviews of the National Public Health Institute of Romania with stakeholders. According to the incidents which occurred in hospitals around the world, a system based on sensors is proposed to mitigate the problems which can appear. The testing of the system was done in laboratory conditions and the reports display the evolution of the measured environmental parameters. The software solution can determine medical professionals to enhance their digital skills and trigger creative ideas to improve the experience of their patients.